The CaM Kinase CMK-1 Mediates a Negative Feedback Mechanism Coupling the C. elegans Glutamate Receptor GLR-1 with Its Own Transcription. - Benjamin J Moss; Lidia Park; Caroline L Dahlberg; Peter Juo (PLoS Genetics, 2016)
Regulation of synaptic AMPA receptor levels is a major mechanism underlying homeostatic synaptic scaling. While in vitro studies have implicated several molecules in synaptic scaling, the in vivo mechanisms linking chronic changes in synaptic activity to alterations in AMPA receptor expression are not well understood. Here we use a genetic approach in C. elegans to dissect a negative feedback pathway coupling levels of the AMPA receptor GLR-1 with its own transcription. GLR-1 trafficking mutants with decreased synaptic receptors in the ventral nerve cord (VNC) exhibit compensatory increases in glr-1 mRNA, which can be attributed to increased glr-1 transcription. Glutamatergic transmission mutants lacking presynaptic eat-4/VGLUT or postsynaptic glr-1, exhibit compensatory increases in glr-1 transcription, suggesting that loss of GLR-1 activity is sufficient to trigger the feedback pathway. Direct and specific inhibition of GLR-1-expressing neurons using a chemical genetic silencing approach also results in increased glr-1 transcription. Conversely, expression of a constitutively active version of GLR-1 results in decreased glr-1 transcription, suggesting that bidirectional changes in GLR-1 signaling results in reciprocal alterations in glr-1 transcription. We identify the CMK-1/CaMK signaling axis as a mediator of the glr-1 transcriptional feedback mechanism. Loss-of-function mutations in the upstream kinase ckk-1/CaMKK, the CaM kinase cmk-1/CaMK, or a downstream transcription factor crh-1/CREB, result in increased glr-1 transcription, suggesting that the CMK-1 signaling pathway functions to repress glr-1 transcription. Genetic double mutant analyses suggest that CMK-1 signaling is required for the glr-1 transcriptional feedback pathway. Furthermore, alterations in GLR-1 signaling that trigger the feedback mechanism also regulate the nucleocytoplasmic distribution of CMK-1, and activated, nuclear-localized CMK-1 blocks the feedback pathway. We propose a model in which synaptic activity regulates the nuclear localization of CMK-1 to mediate a negative feedback mechanism coupling GLR-1 activity with its own transcription.